Forest Cover Change and Legal Pluralism in Forest Management: A Review and Evidence from West Sumatra, Indonesia - R. Rudy; Y. Yonariza; Helvi Yanfika; Ali Rahmat; Winih Sekaringtyas Ramadhani; Abdul Mutolib (Indonesian Journal of Science and Technology, 2021)
This study analyzed the functions of shifting (phenomenon of legal pluralism) and identified forest conversion at Production Forest Management Unit of Dharmasraya (PFMU Dharmasraya), West Sumatra, Indonesia from March 2018 to December 2019 using a qualitative research design with a case study approach. The identification of changes in forest cover analyzed by satellite images using the NDVI method to obtain the distribution of forest cover. Discussion on legal pluralism were examined using a non-ethnographic qualitative research approach through interviews with local communities, companies/permit holders, and related institutions (government). From 2000 to 2019, the PFMU Dharmasraya forest area reduced from 86 to 12%, and plantations increased from 10 to 81% of the total area of 33,539 ha. The legal pluralism of forest ownership occurs because local communities use traditional law, claiming the PFMU Dharmasraya area as Ulayat land. In contrast, the government claims the forest belongs to the state. The motives for the conversion of forest functions are the expansion of oil palm and rubber plantations, forest clearing to mark forest ownership rights, and illegal logging.